2016
DOI: 10.1002/nml.21230
|View full text |Cite
|
Sign up to set email alerts
|

Membership Benefits Matter

Abstract: Professional associations have provided various benefits to their members to bolster member retention and recruitment. This study explored factors that could influence members’ behavioral intentions in professional membership associations by surveying 13,229 members from eighteen associations. More specifically, this analysis focused on the effects of members’ perceptions of the personal and professional benefits offered by associations with which they are affiliated and their satisfaction with those benefits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…The most frequently made suggestions that were noted in the "other" category included member connection with ACA, networking opportunities, insurance, and licensure support. These findings appear to be consistent in other social science fields (see Delmonico, Manderino, & Griffin, 2014;Ki & Wang (2016).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The most frequently made suggestions that were noted in the "other" category included member connection with ACA, networking opportunities, insurance, and licensure support. These findings appear to be consistent in other social science fields (see Delmonico, Manderino, & Griffin, 2014;Ki & Wang (2016).…”
supporting
confidence: 87%
“…For example, Delmonico et al (2014) surveyed members of the Society for the Advancement of Sexual Health (SASH) and they found that the yearly conferences, the Association’s Journal, and the listserv were highly valued resources available through SASH, while resources such as the monthly newsletter were perceived as having lower value. Likewise, Ki and Wang (2016) provided data from 18 professional associations related to human and social sciences. Over “13,000” participants reported that personal and professional identity was positively correlated with their intentions to continue being a member in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Being part of profession and/or professional association brings certain privileges, resources, and powers. 73 , 74 For example, studies have found that being part of a nursing association brings nurses social benefits and support for their ideas. 75 , 76 As noted earlier, the moral anger, contempt and disgust experienced by healthcare workers is likely to, at least partially, emerge from feeling undervalued and unappreciated by their organizations.…”
Section: The Impact Of Negative Moral Emotions On Healthcare Professi...mentioning
confidence: 99%
“…Various reasons drive members' engagement in and with professional associations. Hager (2014) and Ki and Wang (2016) highlight private or personal incentives or benefits members directly receive through their membership in these associations such as job searches, professional networking, or information sharing. These incentives have positive relationships with members' satisfaction and involvement in these organizations and consequently will positively implicate further and future engagements.…”
Section: Understanding Engagementmentioning
confidence: 99%